An Investigation of the Similarities between Iranian and Egyptian Cultures Based on the Study of Lusterware Potteries in the Islamic Middle Ages - Mahla Najarian Tousi; Hassan Hashemi Zarjabad (هنر و تمدن شرق)
With the spread of Islam in the Middle Ages and Iran’s strategic geographic position, interregional communications between Iran and other countries, including Egypt, expanded through trade routes, both overland and maritime. This expansion not only facilitated trade but also led to a significant migration of individuals between Iran and Egypt, fostering regional cultural interactions and exchanges. Pottery is one of the most important and abundant material artifacts in archaeology, and among the significant types of pottery produced in the Islamic Middle Ages is lustreware pottery. This type of pottery, due to its decorative nature and extensive use of intricate patterns in its decoration, has often captured the attention of people and served as a commodity for exchange. Therefore, by studying its iconography, one can discern the extent of cultural interactions between the two regions. This study, conducted through a descriptive-analytical approach using library sources and information from museums worldwide, aims to answer the following question: What similarities exist between Egyptian and Iranian lustreware pottery, and how can we justify the political and cultural exchanges between Egypt and Iran? The findings indicate that many of the patterns found on lustreware pottery in Egypt and Iran are similar, with some common elements resulting from two factors: 1) trade and 2) migration of potters to Iran. The production of lustreware pottery initially served as a luxury item influenced by political factors and tied to governments. Over time, it became accessible to the middle strata of society and enjoyed relative abundance. Therefore, the abundance of this pottery in a region reflects the commercial power and economic prosperity of the government.